Morphology and Phylogeny Reveal Five Novel Species in the Genus Cordyceps (Cordycipitaceae, Hypocreales) From Yunnan, China - Dong, Quan-Ying; Wang, Yao; Wang, Zhi-Qin; Tang, De-Xiang; Zhao, Zhi-Yuan; Wu, Hui-Juan; Yu, Hong (Frontiers in Microbiology, 2022)
The current study was aimed to introduce five new species of Cordyceps from Yunnan, with morphological descriptions, illustrations, color photographs, phylogenetic placement, associated host, and a comparison with allied taxa. The five new species were morphologically distinct from all other Cordyceps sensu lato species, and it was also suggested that they should differ from other species in the genus Cordyceps based on combined multigene analyses. Employing DNA nucleotide sequences of the nrLSU, nrSSU, tef-1α, rpb1 and rpb2, the five new species were recognized in the clade of Cordyceps by using molecular phylogenetic analyses, including five well-supported subclades, such as three new species, Cordyceps bullispora, Cordyceps longiphialis, and Cordyceps nabanheensis were found in the subclade of C. pruinosa, two new species Cordyceps pseudotenuipes and Cordyceps simaoensis were located in the subclade of C. tenuipes. The five novel species shared similar morphologies as other species in the genus Cordyceps, with fleshy and brightly pigmented stromata; perithecia superficial to completely immersed, ordinal in arrangement; hyaline asci, with thickened cylindrical ascus apex. The morphological characteristics of 66 species in Cordyceps sensu stricto, including 5 novel species and 61 known taxa, were also compared.